ANALISIS PENERAPAN PENDIDIKAN KARAKTER GEMAR MEMBACA DI SEKOLAH DASAR NEGERI KEBONSARI 01 TUBAN - Wiratsiwi, Wendri; Elisiana, Dea (Jurnal Muassis Pendidikan Dasar, 2024)
Character education through reading is an important aspect of developing students' personalities. This research aims to determine the implementation of character reading through the literacy program at SDN Kebonsari 01 Tuban. The descriptive method with observation and documentation examines the learning process and student interactions with the school literacy program. The research results show that implementing reading character education through a literacy program positively influences students' reading interests and character development. In addition, literacy programs can significantly improve students' reading and writing skills. These findings contribute to the development of character education like reading through literacy programs in schools. It is hoped that this research can become a reference for other schools to develop literacy programs to improve students' reading abilities.